Non-attendance to the paediatric clinic in Hospital Universiti Sains Malaysia (HUSM) - Mohammad, Jamil (2009)
Non-attendance is suspected to be one of a major problem in Paediatric Clinic. Nonattendance to clinic could lead to severe consequences to the patients and this could give a major burden to the health care system and medical staffs. Several studies have reported more than 30% non-attendance. In Malaysia, there was no similar report found in literature. To determine the rate of non-attendance to Paediatric Clinic HUSM and to determine the efficacy of one telephone call to give a new appointment for every contactable nonattending patient. Methods This study was a cross sectional study. All non-attending patients who had an appointment in the Pediatric Clinic of HUSM during the study period were included in the study from 1 January 2009 to the end of February 2009. Non-attendees who are contactable by telephone were included for the intervention part of the study. A prepared proforma was filled up for every non-attendee. Primary outcome measures included non attendance rate and efficacy of one telephone call to give a new appointment for every contactable non-attending patient. One thousand five hundred and sixty three patients had appointment from January 2009 until end of February 2009 in Paediatric Clinic HUSM. A total of four hundred ninety seven patients (31.8%) were non-attendees. There was significant different in term of clinic sessions, weather condition on the appointment day and types of clinic. From one hundred sixty patients who were successfully contacted, ninety-five patients were interested in new appointment. There were fifty-five patients who had a new appointment already at the time they were contacted. Three of the contactable nonattendees had died at home, three had been admitted, and two had moved to another state and were followed up there. The other two patients were not interested to a new appointment. 23.2% from the intervention group did not attend the clinic after given new appointment. Non-attendance rate is high in Paediatric clinic HUSM and one telephone call is effective in reducing the non-attendance rate.